CLINICAL LEARNING ENVIRONMENT: WHAT DO HOUSE OFFICERS SAY? - Shamsa Humayun (Army Medical College Rawalpindi, 2018)
Objective: To explore effect of format change in house job training and other factors, hindering or promoting junior doctors' training/learning in their transition to practical life. Study Design: Mixed Method Sequential. Place and Duration of Study: Sir Ganga Ram hospital Lahore, from Nov 2011 to Oct 2012. Material and Methods: Four hundred and ninety two doctors completed the modified PHEEM survey after completion of their house job from November 2011 till October 2012 after institutional ethical review Board’s approval. Second phase comprised semi-structured FGD to triangulate findings of the survey with FGD results, to find out, in detail, about doctors’ expectations from their house job training and suggestions for future after ensuring confidentiality and anonymity to study participants. Results: The mean overall score for clinical learning environment was 77.67, implying 57.0% satisfaction. The mean total scores for autonomy; teaching & social support was 25.6, 31.9 & 20.0 respectively. Satisfaction with regard to autonomy, teaching and social support was 25.6/48 (53.3%), 31.9/52 (61.3%) and 20.0/36 (55.5%) respectively. Patterns emerged from FGD were lack of standardization, nonexistence of formative assessment, opportunistic learning, poor quality feedback & inappropriate teaching by medical officers. Skill learning under supervision, confidence in patient management and part of clinical team were motivating factors while poor accommodation, sanitation, catering facilities and short duration of rotation were hindering factors for learning. Conclusion: Evidence generated has shown that internship year was very challenging. Dissatisfaction was expressed with unstructured opportunistic nature of training. Unstructured training program, role ambiguity, substandard physical environment and short duration of rotations were perceived to negatively influence learning. A valued member of clinical team, confidence in patient management, opportunity to acquire procedural skills under supervision and being supported were the factors perceived to enhance learning.